2020
DOI: 10.1371/journal.pone.0231990
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to mold proteases stimulates mucin production in airway epithelial cells through Ras/Raf1/ERK signal pathway

Abstract: Environmental mold (fungus) exposure poses a significant threat to public health by causing illnesses ranging from invasive fungal diseases in immune compromised individuals to allergic hypertensive diseases such as asthma and asthma exacerbation in otherwise healthy people. However, the molecular pathogenesis has not been completely understood, and treatment options are limited. Due to its thermo-tolerance to the normal human body temperature, Aspergillus. fumigatus (A.fumigatus) is one of the most important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Notably, proteases released by Aspergillus fumigatus , a fungus that is highly prevalent in the early CF lung, induce MUC5AC expression [ 66 , 67 ]. A more recent study identified a Ras/Raf1/extracellular signal-regulated kinase (ERK) signalling pathway through which mucin expression was induced by fungal proteases [ 68 ]. Upregulation of MUC5AC by NE and other proteases in CLD will alter the MUC5AC/MUC5B ratio in favour of MUC5AC.…”
Section: Proteases and Mucusmentioning
confidence: 99%
“…Notably, proteases released by Aspergillus fumigatus , a fungus that is highly prevalent in the early CF lung, induce MUC5AC expression [ 66 , 67 ]. A more recent study identified a Ras/Raf1/extracellular signal-regulated kinase (ERK) signalling pathway through which mucin expression was induced by fungal proteases [ 68 ]. Upregulation of MUC5AC by NE and other proteases in CLD will alter the MUC5AC/MUC5B ratio in favour of MUC5AC.…”
Section: Proteases and Mucusmentioning
confidence: 99%
“…Moreover, neither DPI nor NAC inhibited LysoPS-induced MUC5AC production, suggesting that ROS is unlikely to be involved in LysoPS-induced TACE activation. ROS-independent mucin production has also been reported in mold protease-exposed airway epithelial cells [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, Ras, MAPK, and PI3K-Akt signaling pathways have been elucidated in different lung diseases. For example, ERK phosphorylation as a marker of Ras activity has shown prognostic value in non-small cell lung cancer ( 40 ), and exposure to mold proteases stimulated mucin production in airway epithelial cells through Ras/Raf1/ERK signal pathway ( 41 ). Furthermore, Apelin-36 protects against lipopolysaccharide-induced acute lung injury by inhibiting the ASK1/MAPK signaling pathway ( 42 ), whereas fibro growth factor-2 protects against acute lung injury by activating the PI3K/Akt signaling pathway ( 43 ).…”
Section: Discussionmentioning
confidence: 99%